A rapid agroecological mango value chain analysis in Kenya - Onyango, Kevin; Bolo, Peter; Ndiwa, Aurillia; Wanyama, Rosina; Chege, Christine G.K. (2023)
Mango is one of the most important and popular fruit crops in Kenya. It is ranked second after bananas in monetary value (E4C, 2020) and is the third-leading horticultural crop in Kenya, with a total value of 8.6% (HCD, 2020). Since 2010, Kenya has been producing an average of 650,000 metric tons of mangoes annually, which generates an average of USD 84.4 million in gross production value. Recent statistics show that production has increased rapidly since the mid-2000s, growing at a rate of 9.2% per annum, correlating with the increases in mango exports. Mango is largely produced in the Eastern and Coastal regions of Kenya and is dominated by small-scale farmers, who account for 80% of the production, with the remaining distributed among medium- and large-scale producers. It is believed that mangoes were introduced into East Africa around 10th century AD by the Persians. The fruit quickly spread through East African countries, including Kenya, because of its hardy nature and its suitability for different agroecological zones ranging from sub-humid to semi-arid. Mango is a low-calorie fruit that is high in fiber, and is a great source of vitamins A and C. It also contains folate, B6, iron, and a little calcium, zinc, and vitamin E. Makueni County is leading in mango production in Kenya, with an estimated total of 4.3 million trees grown by 28,696 farmers producing approximately 303,000 tons per season. Mango production in the county is concentrated among smallholders, many of whom are in 18 out of 30 wards of the county. Most smallholder farmers cultivate multiple types of crops to help smooth varying production cycles and variable income. Mango is a priority crop in the county given the importance of the value chain to the residents. It is estimated that 61–80% of the Makueni population is directly or indirectly involved in the mango value chain, with an estimated 30% involved in direct production of mangoes (MoALF, 2016).